CO2 greenhouse emissions in Oman over the last forty-two years: Review. (December 2015) - Abdul-Wahab, Sabah A.; Charabi, Yassine; Al-Maamari, Rashid; Al-Rawas, Ghazi A.; Gastli, Adel; Chan, Keziah
Abstract: In the Sultanate of Oman, oil and natural gas related activities have the most important shares of the nation׳s gross domestic product (GDP) and are also the primary cause of greenhouse gas (GHG) emissions within the country. In this study, the CO2 inventory for Oman was developed over the last forty two years (from 1972 to 2013) in accordance with the IPCC reference approach. The results indicated that over the years, the amount of crude oil and natural gas produced and locally consumed in Oman have drastically increased. As a result, CO2 GHG emissions resulting from the consumption of crude oil and natural gas in Oman have also greatly increased. This study aims to assist Oman in monitoring its progress in the reduction of CO2 emissions.